Economic Essence of Resources as an Object of Corporate Management System of the Enterprise - Обельницька, Х. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The author of the article has done a retrospective analysis of the evolution of the scientific thought concerning the notion of ―a resource‖ in order to define its economic content and specify its definition as an object of the system of the corporate governance of an enterprise. The article describes the stages of the revolution of the ideas concerning the resource approach which reveal the importance and significance of enterprise exclusivity formation based on the effective usage of the internal resources of an enterprise. The article is focused on the financial resources of an enterprise which represent the financial relations within an enterprise. The author has done a step-by-step analysis of the definitions concerning the derivation of ―the financial resources of an enterprise‖ and according to the results defined the main features of the term which allows the reader to get a general idea of the derivation studied in the article. The author defines ―the resources of an enterprise‖ as the means and possibilities which are aimed at realizing the objectives set by an enterprise and allowing to design and fulfil the strategies focused on an increase in the effectiveness of its functioning. The author defines ―corporate governance‖ as the combination of elements (including management and coordination bodies, regulations, principles, and rules), the interrelations between them aimed at realizing the process of governance. The article highlights the role of ―a resource‖ regarding it as a basic object of the system of the corporate governance of an enterprise. The article provides the typology of the tasks of a corporate governance system and the presentation of its concrete content.